Uranyl Precipitation by Pseudomonas aeruginosa via Controlled Polyphosphate Metabolism - Renninger, Neil (American Society for Microbiology, 2004)
The polyphosphate kinase gene from Pseudomonas aeruginosa was overexpressed in its native host, resulting in the accumulation of 100 times the polyphosphate seen with control strains. Degradation of this polyphosphate was induced by carbon starvation conditions, resulting in phosphate release into the medium. The mechanism of polyphosphate degradation is not clearly understood, but it appears to be associated with glycogen degradation. Upon suspension of the cells in 1 mM uranyl nitrate, nearly all polyphosphate that had accumulated was degraded within 48 h, resulting in the removal of nearly 80% of the uranyl ion and >95% of lesser-concentrated solutions. Electron microscopy, energy-dispersive X-ray spectroscopy, and time-resolved laser-induced fluorescence spectroscopy (TRLFS) suggest that this removal was due to the precipitation of uranyl phosphate at the cell membrane. TRLFS also indicated that uranyl was initially sorbed to the cell as uranyl hydroxide and was then precipitated as uranyl phosphate as phosphate was released from the cell. Lethal doses of radiation did not halt phosphate secretion from polyphosphate-filled cells under carbon starvation conditions.